Chromosome-Level Assembly and Annotation of the Genome of the Endangered Giant Patagonian Bumble Bee Bombus dahlbomii - Martínez, Lican Ernesto (2024)
This article describes a genome assembly and annotation for Bombus dahlbomii, the giant Patagonian bumble bee. DNA from a single, haploid male collected in Argentina was used for PacBio (HiFi) sequencing, and Hi-C technology was then used to map chromatin contacts. Using Juicer and manual curation, the genome was scaffolded into 18 main pseudomolecules, representing a high-quality, near chromosome-level assembly. The sequenced genome size is estimated at 265 Mb. The genome was annotated based on RNA sequencing data of another male from Argentina, and BRAKER3 produced 15,767 annotated genes. The genome and annotation show high completeness, with >95% BUSCO scores for both the genome and annotated genes (based on conserved genes from Hymenoptera). This genome provides a valuable resource for studying the biology of this iconic and endangered species, as well as for understanding the impacts of its decline and designing strategies for its preservation.